Association between pupil dilation and implicit processing prior to object recognition via insight - Suzuki, Yuta (Sci Rep, 2018)
Insight refers to the sudden conscious shift in the perception of a situation following a period of unconscious processing. The present study aimed to investigate the implicit neural mechanisms underlying insight-based recognition, and to determine the association between these mechanisms and the extent of pupil dilation. Participants were presented with ambiguous, transforming images comprised of dots, following which they were asked to state whether they recognized the object and their level of confidence in this statement. Changes in pupil dilation were not only characterized by the recognition state into the ambiguous object but were also associated with prior awareness of object recognition, regardless of meta-cognitive confidence. Our findings indicate that pupil dilation may represent the level of implicit integration between memory and visual processing, despite the lack of object awareness, and that this association may involve noradrenergic activity within the locus coeruleus-noradrenergic (LC-NA) system.